2003
DOI: 10.1177/0272431603254292
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Parental Depressed Mood for Young Adolescents' Emotional and Family Experiences

Abstract: Drawing from a larger longitudinal investigation, the links between young adolescents' everyday experiences and parental depressed mood were examined in 201 primarilyCaucasian family groups. The current study used data collected when the adolescents were in seventh and eighth grade. Families in which at least one parent reported recurrent depressed mood (n = 36) were compared with a contrast group of families (n = 165). Adolescents in the recurrent parent depression group reported higher levels of depressed mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…For example, it might be that specific subgroups benefit more than others from stronger adherence. Finally, because research has indicated that caregiver functioning can influence child functioning (e.g., Sarigiani, Heath, & Camarena, 2003), further investigation into how adherence to the system of care philosophy also might improve caregiver functioning, in addition to child functioning, is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it might be that specific subgroups benefit more than others from stronger adherence. Finally, because research has indicated that caregiver functioning can influence child functioning (e.g., Sarigiani, Heath, & Camarena, 2003), further investigation into how adherence to the system of care philosophy also might improve caregiver functioning, in addition to child functioning, is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…"Being a frustrated observer" described how children were focused on the repercussions of their parent's mood on their own and the family's life, and their sense of loneliness led to a family life situation inconsistent with their emotional and social needs (Sarigiani et al, 2003). A yearning for reciprocity arose since children felt rejected by their parent as they drifted apart because of MDD, and a sense of loneliness made itself felt in their family life.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of MDD have an intrusive impact on men and women and their capacity to perform normally on an individual basis as well as in family life (Gross, Conrad, Fogg, & Wothke, 1994;Judd et al, 2008;Kornstein et al, 2000), and children respond to their parent's MDD by developing symptoms related to psychopathology (Langrock, Compas, Keller, Merchant, & Copeland, 2002). When the daily experiences of young adolescents regarding parents' depressed mood were investigated (Sarigiani, Heath, & Camarena, 2003), those whose parent suffered from recurrent depression were reported to be more depressed and to experience more family conflicts compared to adolescents in families without parental mood problems. How children and adolescents coped with parental depression was investigated by Jaser et al (2005).…”
mentioning
confidence: 99%
“…McAdamsetal.,2015 (Sarigiani, Heath, &Camarena, 2003). Η γνληθή θαηάζιηςε νδεγεί ζε αύμεζε ηνπ ζηξεο ζηελ νηθνγέλεηα θαη πξνθαιεί αξλεηηθέο αιιειεπηδξάζεηο παηδηώλ-γνλέσλ, ραξαθηεξηζηηθά ηα νπνία ζπλδένληαη κε ηελ απνζηαζηνπνίεζε, ηελ απνθπγή, ηελ ερζξόηεηα θαη ηελ επεξεζηζηόηεηα ησλ δεύηεξσλ (Lovejoy etal., 2000).…”
Section: ειζαγφγικάunclassified